Analisis Yuridis Mengenai Perbedaan Pertimbangan Putusan Hakim Pengadilan Tingkat Pertama dan Tingkat Kasasi terhadap Tindak Pidana Pemalsuan Dokumen Kepabeanan (Studi Kasus Putusan Nomor 185/PID.SUS/2016/PN.JAK.UTR dan Putusan Nomor 294 K/PID.SUS/2018) - Ni Nyoman Ari Triantari; Junior B Gregorius (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the decisions of judges at the First Instance Court and the Cassation Level related to the crime of forgery of customs documents in Decision Number 185/PID.SUS/2016/PN.JAK.UTR and Decision Number 294 K/PID.SUS/2018. This study uses the Normative Juridical Legal Research Method by utilizing laws and regulations and judges' decisions and using the theory of criminal acts and the theory of punishment. The formulation of the problem in this study is, how is the consideration of the Panel of Judges at the First Instance Court so that the defendant is released from all charges by the Public Prosecutor, and how are the arguments of the Public Prosecutor's cassation memorandum and the legal considerations of the Panel of Judges at the Cassation level so that they impose a criminal sentence on the defendant. This study found that, the legal considerations of the Panel of Judges in Decision Number 185/PID.SUS/2016/PN.JAK.UTR which acquitted the Defendant from all charges of the Public Prosecutor because according to the Panel of Judges' considerations, all the tools and evidence revealed in the trial were in accordance with the provisions of the Criminal Procedure Code, both Article 184 of the Criminal Procedure Code and the conviction of the judge referred to in the provisions of Article 183 of the Criminal Procedure Code, and according to the theories of criminal acts and theories of punishment that the Defendant was not legally and convincingly proven to have committed the crime of falsifying customs documents. The arguments of the Public Prosecutor's cassation memorandum emphasize that Judex Facti applied the law incorrectly so that the Legal Considerations of the Panel of Judges of the Supreme Court in the Cassation Decision Number: 294 K/PID.SUS/2018 imposed a criminal sentence on the defendant because the Panel of Judges of the first instance (Judex Facti) applied the law incorrectly, therefore the Defendant was proven legally and convincingly guilty of jointly committing the crime of falsifying Customs documents as stipulated in Article 103 letter a of Law of the Republic of Indonesia Number 10 of 1995 concerning customs, as amended by Law Number 17 of 2006 in conjunction with Article 55 Paragraph (1) KE-1 of the Criminal Code.